Multiscale modelling of biopolymers - Scacchi, A.; Vuorte, M.; Sammalkorpi, M. (Taylor and Francis Ltd., 2025)
This review overviews common biopolymer modelling approaches ranging from chemically specific to highly coarse-grained techniques, along with their application ranges, strengths and limitations. Recent modelling applications at each modelling scale are outlined and discussed. The focus is on modelling of protein and peptide, nucleic acid and saccharide-based biopolymer systems, excluding lignocellulose materials. The survey focuses on physics-based models. We cover particle-based simulations methods, including all-atom and coarse-grained molecular dynamics (MD), dissipative particle dynamics (DPD) and Langevin and Brownian dynamics (BD) approaches. While these methods capture molecular and particle-level dynamics, a brief overview of also stochastic sampling approaches (Monte Carlo methods) to physics-based models, as well as free energy functional-based methods, i.e. field theory approaches, such as self-consistent field theory (SCFT) and classical density functional theory (cDFT), are provided.